Self-excited brillouin–erbium fiber laser for DWDM applications - HARUN, S; CHENG, X; POOPALAN, P; AHMAD, H (ELSEVIER SCI LTD, 2007)
The operation of the self-excited Brillouin/erbium fiber laser (BEFL) is experimentally demonstrated. It uses a forward pumped erbium-doped fiber (EDF) as a gain medium to generate a Brillouin-pump (BP) and amplify the Stokes frequency signals generated in a single-mode fiber (SMF). The operating wavelength varies with changes of coupling ratio of the looping arm. The optimum BEFL operation is obtained with a center wavelength at 1567.5 nm by looping back 20% of BEFL output into the other end of the SMF. The BEFL output power and number of lines increases gradually as 980-nm pump power increases. At the maximum 980-nm pump power of 118 mW, a stable and strong BEFL comb of up to 16 lines with 11 GHz spacing is demonstrated. The self-excited BEFL has the potential to be used in the future dense wavelength division multiplexing (DWDM) communication system. (c) 2005 Elsevier Ltd. All rights reserved.